The Strength of Strong Ties: Social Networks and Intergroup Conflict in Organizations - Nelson, Reed Elliot (Academy of Management Journal, 1989)
The relationship between social networks and conflict in 20 organizational units was investigated. Results indicated that low-conflict organizations are characterized by higher numbers of intergroup strong ties, measured as frequent contacts, than are high-conflict organizations. Further, comparison of the network configuration of the organizations studied suggested that high- and low-conflict organizations feature significantly different sociometric structures.